Unraveling Consumer Mindset: Analysis of Consumer Behavior in the Distribution of E-WOM on The Originote Skincare Product - Qurrotul Aini, Nurul; Nur Oktaviani, Fadhilah; Sudarmiatin, Sudarmiatin (Lafadz Jaya Publisher, 2025)
This study aims to analyze the spread of e-WOM on the skincare brand